2010
DOI: 10.5194/npg-17-177-2010
|View full text |Cite
|
Sign up to set email alerts
|

The role of mesoscale eddies time and length scales on phytoplankton production

Abstract: Abstract. Horizontal mixing has been found to play a crucial role in the development of spatial plankton structures in the ocean. We study the influence of time and length scales of two different horizontal two-dimensional (2-D) flows on the growth of a single phytoplankton patch. To that end, we use a coupled model consisting of a standard three component ecological NPZ model and a flow model able to mimic the mesoscale structures observed in the ocean. Two hydrodynamic flow models are used: a flow based on G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The study also concluded that the correlation between Eulerian diagnostics and Lyapunov exponents does not hold when basin-scale climatologies are computed by averaging submesoscale-resolving maps. Transport barriers derived from altimetry by computing the finite-size Lyapunov exponent have been compared to satellite-derived [39,38] and modelled [57] chlorophyll patches. These comparisons showed the structuring role of stirring on primary production and in particular provided evidence of how the temporal variability of the mesoscale velocity field can break closed orbits associated with mesoscale eddies and create submesoscale spiralling patterns visible in satellite chlorophyll images.…”
Section: Satellite Altimetry and The Lyapunov Exponent Calculationmentioning
confidence: 99%
“…The study also concluded that the correlation between Eulerian diagnostics and Lyapunov exponents does not hold when basin-scale climatologies are computed by averaging submesoscale-resolving maps. Transport barriers derived from altimetry by computing the finite-size Lyapunov exponent have been compared to satellite-derived [39,38] and modelled [57] chlorophyll patches. These comparisons showed the structuring role of stirring on primary production and in particular provided evidence of how the temporal variability of the mesoscale velocity field can break closed orbits associated with mesoscale eddies and create submesoscale spiralling patterns visible in satellite chlorophyll images.…”
Section: Satellite Altimetry and The Lyapunov Exponent Calculationmentioning
confidence: 99%
“…Horizontal transport through mesoscale hydrodynamic structures such as vortices leads to a redistribution of nutrients and plankton and can cause several interesting phenomena (Abraham, 1998;López et al, 2001;Martin and Pondaven, 2003;Tél et al, 2005;Sandulescu et al, 2007Sandulescu et al, , 2008Rossi et al, 2008;Maraldi et al, 2009;Bracco et al, 2009). A very important role in understanding these phenomena is played by the interplay of hydrodynamic and biological time scales (Abraham, 1998;Richards and Brentnall, 2006;Sandulescu et al, 2007;Pérez-Muñuzuri and Huhn, 2010). By modeling plankton growth in Correspondence to: D. Bastine (david.bastine@uni-oldenburg.de) a simplified model for turbulent advection Abraham (1998) showed that this interplay can help to explain the patchiness of plankton distributions observed in the ocean.…”
Section: Introductionmentioning
confidence: 99%
“…LCS analysis has been used in the study of marine trophic dynamics, with some evidence of predators using LCS to find prey (Kai et al ; d'Ovidio et al ). LCS analysis has also aided in understanding the effects of ocean currents on phytoplankton distributions (Perez‐Munuzuri and Huhn ) and harmful algal blooms (Olascoaga et al ). The resolution, and subsequent detection, of LCS depends on the total integration time, initial particle density, and the temporal and spatial resolutions of the underlying velocity field (see Discussion in Carlson et al ()).…”
Section: Analysis and Visualizationmentioning
confidence: 99%